BIOCHEMICAL INVESTIGATION ON THE EDIBLE MOLLUSCS OF KERALA II. A STUDY ON THE NUTRITIONAL VALUE OF SOME GASTROPODS AND CEPHALOPODS - SURYANARAYANAN, H; KUMARI, R SHYLAJA; ALEXANDER, K M (Fishery Technology, 2016)
Data on the biochemical composition and food value of the edibleportions of two gastropods, Pila virens and Achatina fulica and twocephalopods, Sepiella inermis and Loigo indica have been presented.These molluscs posses nutritive meat very rich in protein and minerals,which compare favourably with popular food fishes in caloricvalue. The significance of the variations met with in the biochemicalconstituents of the different species has been di~cussed.